Numerical geometry, grid generation and scientific computing : proceedings of the 9th International Conference, NUMGRID 2018 / Voronoi 150, celebrating the 150th anniversary of G.F. Voronoi, Moscow, Russia, December 2018 /: proceedings of the 9th International Conference, NUMGRID 2018 / Voronoi 150, celebrating the 150th anniversary of G.F. Voronoi, Moscow, Russia, December 2018. (2019) - Unknown
No abstract available